Balloon burster: A CORBA-based visual servoing for humanoid robot in a distributed environment - Lee, J.; Jie, M.; Kim, S.; Jung, M.; Kim, C.; You, B. (Proceedings of the SICE Annual Conference, 2007)
This paper proposes CORBA-based visual servoing system of humanoid robot. To effectively control the humanoid robot which is connected to network, it needs to define necessary services for visual servoing as distribution object, and realize them in the middleware. For realizing it following services should be addressed. Naming service for searching a necessary service with unique name assigned to each object, image service for supplying image obtained from stereo camera. In the experiment, we show the result of balloon tracking and bursting mat the robot tracks balloons as target objects in the real time, and if a balloon stop for a certain time, then the robot bursts the balloon. ？ 2007 SICE.